2004
DOI: 10.1002/mabi.200300093
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Alloys of Nodax Copolymers and Poly(lactic acid)

Abstract: Properties of polymer alloys comprising poly(lactic acid) and Nodax copolymers are investigated. Nodax is a family of bacterially produced polyhydroxyalkanoate (PHA) copolymers comprising 3-hydroxybutyrate (3HB) and other 3-hydroxyalkanoate (3HA) units with side groups greater than or equal to three carbon units. The incorporation of 3HA units with medium-chain-length (mcl) side groups effectively lowers the crystallinity and the melt temperature, Tm, of this class of PHA copolymers, in a manner similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(193 citation statements)
references
References 10 publications
8
181
4
Order By: Relevance
“…Similar results have been reported by Noda et al 36 They investigated the properties of blends of poly(lactic acid), which is hard and brittle, and a class of PHAs called Nodax. It was found that the addition of a small amount of PHAs effectively improved the toughness of poly(lactic acid) by inducing crazing deformation rather than the typical brittle fracture.…”
Section: Microscopic Observationsupporting
confidence: 84%
“…Similar results have been reported by Noda et al 36 They investigated the properties of blends of poly(lactic acid), which is hard and brittle, and a class of PHAs called Nodax. It was found that the addition of a small amount of PHAs effectively improved the toughness of poly(lactic acid) by inducing crazing deformation rather than the typical brittle fracture.…”
Section: Microscopic Observationsupporting
confidence: 84%
“…29 PHAs that consist of 3HB and a small amount of MCL-HA units have lower crystallinities and T m s and more ductile properties than short-chain-length PHAs. Noda et al 30 reported that blends of PLA with this type of PHA can form an excellent pair of complementary materials, which can effectively balance the shortcomings of these materials when combined. For example, the results indicated that the toughness and elongation at break of the blends significantly improved when 10% of PHA was added to PLA, which was attributed to an increase in the amorphous phase of the blends and caused unusually slow crystallization kinetics of finely dispersed PHA particles.…”
Section: Pha Modification Via Blendingmentioning
confidence: 99%
“…PHAs composed of monomers bearing a side chain of medium chain length (mclPHAs) have been reported to exhibit low glass transition temperatures (T g ), and have been used as additives to reduce the stiffness of PLLA (Noda et al 2004). Even when a small quantity (10-20 wt%) of mcl-PHA was mixed with PLLA, the properties of PLLA were dramatically improved.…”
Section: Discussionmentioning
confidence: 99%